Training On Organic Waste Management Into Liquid Fertilizer To Improve Residents' Economy - Natasya, Adelia; Penola, Yola; F.A, Raden Ajeng Flaura; Subagia, Nyoman Gede; Nugroho , Husnul; Damarsiwi , Eska Prima Monique; Yulianti, Liza; Susanti, Neri (Universitas Dehasen Bengkulu, 2025)
The training activity on managing organic waste into fertilizer was carried out as an effort to empower the community of RT 02 RW 01 Pematang Gubernur Village in improving family economy while reducing the volume of household waste. Organic waste, which generally comes from food scraps and kitchen waste, has great potential to be processed into liquid fertilizer that has economic value. This training aims to provide understanding and practical skills to residents in processing organic waste in a simple and sustainable way. Training methods include counseling, demonstrations, and direct practice. The results of the activity showed an increase in knowledge and ability of residents in producing liquid fertilizer, as well as the emergence of initiatives to sell processed products as an additional source of income. Thus, this training contributes positively to increasing environmental awareness and empowering the local community's economy.